Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.